Psychological Capital, Organizational Commitment, and Tour Guide Retention Intention: An Investigation in the Context of the COVID-19 Pandemic an Empirical Study in Taiwan - Chang, Nai-Wen; Liu , Ching-Huei; Chen, Shiu-Hua (International Journal of Membrane Science and Technology, 2023)
This study explores the relationship between psychological capital, organizational commitment, and job retention intentions among tour leaders in the tourism industry. Drawing upon the framework of organizational behavior, we examine the effects of psychological capital and organizational commitment on tour leaders' job retention intentions, particularly in the context of the COVID-19 pandemic. A sample of 149 tour leaders participated in the study. Structural equation modeling (SEM) incorporating regression and path analysis was utilized to analyze the data. The empirical results support the hypothesis that psychological capital, specifically self-efficacy and hope optimism, positively influence tour leaders' organizational commitment. Furthermore, organizational commitment, consisting of continuance commitment and affective commitment, was found to positively impact tour leaders' job retention intentions. Normative and affective organizational commitments were identified as mediators in the relationship between psychological capital and job retention intentions. The findings contribute to the understanding of the role of psychological capital and organizational commitment in shaping job retention intentions among tour leaders in the tourism industry. This study offers theoretical insights and practical implications for tour leaders, management, and scholars in the field.